Suboptimal push‐out bond strengths of calcium silicate‐based sealers. (1st September 2015) - Oliveira, D. S.; Cardoso, M. L.; Queiroz, T. F.; Silva, E. J. N. L.; Souza, E. M.; De‐Deus, G.
Abstract: Aim: To evaluate and compare the push‐out bond strength of MTA Fillapex (Angelus, Londrina, Brazil) and iRoot SP (Innovative BioCeramix Inc., Vancouver, Canada) to the dentine walls of root canals. AH Plus (Dentsply DeTrey, Konstaz, Germany) and MTA (Angelus, Londrina, Brazil) were used as reference materials. Methodology: Sixty extracted human single‐rooted teeth were selected. After standardized canal preparation and irrigation, the canals were dried with paper points and filled with one of four sealers: AH Plus, iRoot SP, MTA and MTA Fillapex. Roots were sectioned, and push‐out tests were performed. The values of bond strength were analysed using the Kruskal–Wallis test. Mann–Whitney with Bonferroni correction was used to isolate the differences. The alpha‐type error was set at 0.05 for the analyses. Results: All specimens had measurable adhesion to root dentine and no premature failure occurred. There were significant differences amongst materials ( P = 0.000). MTA‐filled specimens had higher push‐out bond strength values ( P = 0.000). AH Plus had significantly higher bond strength than both Fillapex and iRoot SP ( P = 0.000). Both Fillapex and iRoot SP had the lowest push‐out bond strength amongst all experimental groups ( P = 0.000). No difference occurred between the two calcium silicate‐based root canal sealers ( P = 0.265). Conclusion: The adhesion to root dentine associated with newer calcium silicate‐based sealers was compromised even when well‐monitored laboratory conditions were used.